2009
DOI: 10.1007/s12088-009-0022-0
|View full text |Cite
|
Sign up to set email alerts
|

Microbial diversity in firework chemical exposed soil and water samples collected in Virudhunagar district, Tamil Nadu, India

Abstract: Microbial diversity of soil and water samples collected from pyrochemicals exposed areas of Virdhunagar district (Tamil Nadu, India) was studied. Soil and water samples from cultivable area, waste land and city area of the same region were also studied for a comparative acount. There is a remarkable reduction in total heterotrophic bacterial population (THB) in pyrochemicals exposed soil and water samples (42 × 10 4 CFU/g and 5.6 × 10 4 CFU/ml respectively), compared to the THB of cultivable area soil and wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
1
1
0
1
Order By: Relevance
“…In addition, pyrochemicals are known to act on microbes either as free radical or in molecular state, thus destructing the cell wall or the genetic material (Kim et al., 2016). The results of the present study correlate with a previous one which ascertained the impact of pyrochemicals on microbial diversity in soil, leading to reduction in bacterial count (Dhasarathan et al., 2010).…”
Section: Resultssupporting
confidence: 91%
“…In addition, pyrochemicals are known to act on microbes either as free radical or in molecular state, thus destructing the cell wall or the genetic material (Kim et al., 2016). The results of the present study correlate with a previous one which ascertained the impact of pyrochemicals on microbial diversity in soil, leading to reduction in bacterial count (Dhasarathan et al., 2010).…”
Section: Resultssupporting
confidence: 91%
“…It can be seen that both the EIF and the WIF fields were dominated by Bacillus and Bacillus-derived genera. These genera have been reported inhabiting industrial effluents [22] contaminated water samples [23]. They play a potential role in kraft lignin degradation [24], and therefore it is not with great surprise that these genera were found in the effluent irrigated samples.…”
Section: Phylogenetic Analysis Of Bacterial Isolatesmentioning
confidence: 96%
“…Estos valores son claramente superiores a lo reportado por Wan et al, (2015) y están con la quema masiva de fuegos artificiales para conmemorar las festividades de primavera durante esos meses. Dhasarathan et al, (2010) Dhasarathan et al, (2010) observed that in soil Information given in Table 5 de contaminantes en diversas festividades mexicanas, (ii) análisis de la composición y concentración de metales en el material particulado, (iii) cuantificación de la emisión de gases de efecto invernadero, (iv) análisis de contenido de perclorato en suelos y cuerpos de agua y (v) calcular el porcentaje de contaminación atmosférica por quema masiva de pirotecnia con respecto al total de la contaminación atmosférica.…”
Section: Soil Contaminationunclassified